The bad butterfly - Rippin, Sally; Fukuoka, Aki, 1982- (Tulsa, OK : Kane Miller, 2012)
Billie has started ballet classes. She wants to be a great dancer, but is she really cut out to be a ballerina?
First published: Australia : Hardie Grant Egmont, 2010.
Keywords: Girls -- Juvenile fiction; Dance -- Juvenile fiction; Girls -- Fiction; Dance -- Fiction